2002
DOI: 10.1067/mva.2002.120034
|View full text |Cite
|
Sign up to set email alerts
|

Durability of benefits of endovascular versus conventional abdominal aortic aneurysm repair

Abstract: Although initial LOS was shorter for the patients who underwent endovascular as compared with conventional AAA repair, this advantage was lost during the follow-up interval because of frequent readmission for the treatment of procedure-related complications, chiefly endoleak. These readmissions frequently involved the performance of additional invasive procedures. Gender differences existed regarding LOS and the likelihood of complications after open and endovascular AAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 49 publications
(50 reference statements)
4
63
1
1
Order By: Relevance
“…According to data reported by Anderson (402)(403)(404). Nevertheless, these and other studies (405)(406)(407) also have suggested that the total costs of endovascular repair probably exceed those for open repair, especially when the expense of subsequent follow-up imaging, further intervention, and secondary hospital admissions is added to the base cost ($6000 to $12 000 U.S. dollars) of most endografts. Despite the shorter length of stay and earlier return to normal activity associated with aortic endografting, this procedure does not appear to be associated with superior late functional outcome or longer qualityadjusted life expectancy compared with open surgical treatment (408,409).…”
Section: Early Mortality and Complication Ratesmentioning
confidence: 86%
“…According to data reported by Anderson (402)(403)(404). Nevertheless, these and other studies (405)(406)(407) also have suggested that the total costs of endovascular repair probably exceed those for open repair, especially when the expense of subsequent follow-up imaging, further intervention, and secondary hospital admissions is added to the base cost ($6000 to $12 000 U.S. dollars) of most endografts. Despite the shorter length of stay and earlier return to normal activity associated with aortic endografting, this procedure does not appear to be associated with superior late functional outcome or longer qualityadjusted life expectancy compared with open surgical treatment (408,409).…”
Section: Early Mortality and Complication Ratesmentioning
confidence: 86%
“…4,9,[42][43][44][45][46][47][48][49][50][51] In any case, the technique incorporates an extra-anatomic bypass and should be reserved for unfavorable anatomies and patients unfit for open repair. …”
Section: Discussionmentioning
confidence: 99%
“…Midterm results of EVAR are sufficiently encouraging to justify the choice of the procedure [1][2][3][4][5][6][7][8] ; however, the long-term verdict is still unclear. [9][10][11][12][13][14][15] Endografting with a bifurcated endoprosthesis is contraindicated in certain patients due to various anatomic restrictions.…”
mentioning
confidence: 99%
“…Persistent endoleak, device migration, and limb thrombosis were common causes for these procedures, approximately 25% of which were open surgical and 75% were endovascular procedures (205). The most common indication for secondary intervention is type II endoleak.…”
Section: Secondary Interventionsmentioning
confidence: 98%